Spermatogenesis and nucleolar activity in Triatoma klugi (Triatomine, Heteroptera) - da Costa, Laiana Cristina [UNESP]; Vilela de Azeredo-Oliveira, Maria Tercilia [UNESP]; Tartarotti, Ester [UNESP] (Soc Brasil Genetica, 2008)
Triatoma klugi is a Chagas disease vector in the Rio Grande do Sul State. Triatominae chromosomes are holocentric and sex chromosomes segregation is post-reductional. In this paper we describe the karyotype of male T. klugi and a meiotic analysis including the nucleolar behavior during spermatogenesis. Testis cells were analyzed after lacto-acetic orcein and silver nitrate staining. Two autosomes and the heterochromosomes presented nucleolar activity (Ag-NORs) during diplotene-diakinesis. The analysis of metaphase I and II revealed a karyotype with 2n = 20+XY. In metaphase I a prominent nucleolar mass was observed in the cell periphery and small silver grains were detected in metaphase II. During anaphase, the chromosomes segregated in parallel and a typical holocentric late migration behavior was observed. The restoration of the nucleolus was an important feature in this phase. During telophase nucleolar masses persisted and in early spermiogenesis the spermatids presented a small peripheral mass until elongation. The present study is a contribution to the study of chromatin behavior and nucleolar persistence in meiosis.
Keywords: Triatoma klugi; Triatomine; Cytogenetic; Nucleolus; Karyotype; Meiosis